Early-strength low-resilience sprayed concrete material and preparation method thereof

By adding sodium alginate and sodium carboxymethylcellulose into the modified accelerator of early-high strength and low rebound jet concrete materials, and using magnetic silica nanowires, the fluorosilicate accelerator in the prior art was solved. The strength reduction and durability problems caused by the agent achieve high strength and good durability of concrete materials.

CN119430799AActive Publication Date: 2025-02-14CHINA RAILWAY FIRST GRP SECOND ENG CO LTD

Patent Information

Application Number
CN202411604886.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-14
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

When using fluorosilicate quick-setting agents, existing early high strength and low rebound jet concrete materials lead to a decrease in final compressive strength and flexural strength, and poor corrosion resistance and permeability resistance, and long-term strength.

Method used

By adding sodium alginate and sodium carboxymethylcellulose to the modification accelerator, and magnetic silica nanowires are added to the concrete material, a stable gel state is formed, and the strength and durability of the concrete are improved.

Benefits of technology

The rapid gel formation of concrete materials is achieved, reducing rebound, improving compressive strength and flexural strength, improving corrosion resistance and permeability, thereby improving the overall performance of concrete materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430799A_ABST
    Figure CN119430799A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of road building materials, in particular to an early-strength low-resilience sprayed concrete material and a preparation method thereof. The preparation method comprises the following steps: preparing the modified accelerator; preparing a silicon dioxide nanowire; preparing a magnetic silicon dioxide nanowire; and preparing the early-strength low-resilience shotcrete material. Sodium alginate and sodium carboxymethyl cellulose are added in the preparation of the modified accelerator, the sodium alginate and the sodium carboxymethyl cellulose can cooperate with each other when being used together, a colloidal network formed by the sodium alginate can wrap and stabilize particles of a dispersed phase, and the particles of the dispersed phase can be dispersed by the sodium carboxymethyl cellulose through winding and interweaving of macromolecular chains of the sodium carboxymethyl cellulose. The viscosity and the stability of the dispersion system are further enhanced, so that the concrete material quickly forms a gel state, the resilience is reduced, and the concrete strength is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of road construction materials, and in particular to an early high-strength low-rebound shotcrete material and a preparation method thereof. Background Art

[0002] Early high-strength and low-rebound shotcrete material is a high-performance concrete material developed to meet special engineering needs. It is especially suitable for rapid construction occasions such as mines, tunnels, underground projects and emergency repairs. In order to achieve sufficient strength in a short time so as to carry subsequent construction or restore traffic as soon as possible and reduce the construction period, high-strength and low-rebound shotcrete generally uses fast-hardening or extra-fast-hardening cement as the basis. Sometimes mineral admixtures such as silica fume and slag powder are added to adjust the early strength and working performance, and accelerators are also added to speed up the setting speed.

[0003] The prior art adds an accelerator prepared by fluorosilicic acid to an early high-strength and low-rebound shotcrete material to increase the setting speed of the concrete. However, the fluorosilicate accelerator may cause the ultimate compressive strength and flexural strength of the concrete to be lower than those of conventional concrete. Concrete using the fluorosilicate accelerator often exhibits poor corrosion resistance and impermeability, thereby reducing its long-term strength. Therefore, the present invention provides an early high-strength and low-rebound shotcrete material and a preparation method thereof to solve the problems existing in the prior art. Summary of the invention

[0004] In view of the deficiencies in the prior art, the object of the present invention is to provide an early high-strength low-rebound shotcrete material and a preparation method thereof.

[0005] A method for preparing an early high-strength low-rebound shotcrete material comprises the following steps:

[0006] S1: Preparation of modified accelerating agent

[0007] Fluorosilicic acid is added to a reactor, and aluminum hydroxide is slowly added, and magnetic stirring is performed to obtain a suspension, deionized water is heated, aluminum sulfate is added, and then the suspension and sodium aluminate are added, and the mixture is stirred evenly and heated to react to obtain a reaction solution, sodium alginate and sodium carboxymethyl cellulose are added to the reaction solution, and the reaction solution is cooled, and stirring is maintained during the cooling process until the reaction solution is cooled to room temperature to obtain an accelerating setting agent, and nano-silicon dioxide is added to the accelerating setting agent, and the mixture is stirred evenly to obtain a modified accelerating setting agent;

[0008] S2: Preparation of silica nanowires

[0009] Mixing ionized water, sodium citrate solution, anhydrous ethanol, 25% ammonia water and 50% polyvinyl pyrrolidone ethanol solution to obtain a microemulsion, adding TEOS to the microemulsion, heating the reaction to obtain a white product, washing the white product with anhydrous ethanol and deionized water, and drying to obtain silica nanowires;

[0010] S3: Preparation of magnetic silica nanowires

[0011] The silica nanowires are immersed in deionized water, ultrasonically dispersed, and purged with nitrogen to obtain treated silica nanowires, FeCl3·6H2O and FeSO4·7H2O are mixed and added to deionized water, purged with nitrogen, and then the treated silica nanowires are added thereto, heated in a water bath, and ammonia water is added during stirring to obtain a final mixture, and then the final mixture is kept in a water bath at 65° C. for 2 hours, and finally thoroughly washed with water to neutrality, and dried to obtain magnetic silica nanowires;

[0012] S4: Preparation of early high-strength and low-rebound shotcrete materials

[0013] 100 parts by mass of silicate cement, 10-15 parts by mass of fly ash, 15-40 parts by mass of calcium carbonate, 1-1.5 parts by mass of carbon fiber, 4-7 parts by mass of magnetic silica nanowires, 10-15 parts by mass of polycarboxylate water reducer, 25-35 parts by mass of modified accelerator and 150-200 parts by mass of mixing water are mixed for 30-35 minutes to obtain an early high-strength low-rebound shotcrete material.

[0014] Furthermore, step S1 of preparing a modified quick-setting agent comprises the following steps:

[0015] S1.1: Take 50 parts by mass of fluorosilicic acid and add it into a reactor, and slowly add 25 parts by mass of aluminum hydroxide, stir with a magnetic stirrer at 150-200 r / min for 30-35 min to obtain a suspension;

[0016] S1.2: Heat 200 parts by weight of deionized water to 60-65°C, add 84-85 parts by weight of aluminum sulfate while stirring, continue stirring until the aluminum sulfate is dissolved, then add 17 parts by weight of the suspension and 1.7 parts by weight of sodium aluminate, stir evenly, heat the solution to 80-85°C, keep warm and react for 30-40 minutes to obtain a reaction solution;

[0017] S1.3: Add 1 part by mass of sodium alginate and 2 parts by mass of sodium carboxymethyl cellulose to the reaction solution, and cool it at 0-4°C. Stir the mixture until it cools to room temperature to obtain an accelerating setting agent.

[0018] S1.4: Add 1.5-4.5% by mass of nano-silicon dioxide to the accelerating setting agent, stir evenly, and obtain a modified accelerating setting agent.

[0019] Furthermore, in step S1.4, the diameter of the nano-silicon dioxide is 20-50 nm.

[0020] Furthermore, step S2 of preparing silicon dioxide nanowires comprises the following steps:

[0021] S2.1: Mix ionized water, sodium citrate solution, anhydrous ethanol, 25% ammonia water and 50% polyvinylpyrrolidone ethanol solution in a volume ratio of 3:1:10:1:100 to obtain a microemulsion;

[0022] S2.2: Add TEOS to the microemulsion, raise the temperature to 40°C, and centrifuge at 800-1000 r / min for 10-15 min, react for 4 h, and obtain a white product;

[0023] S2.3: The white product was washed with anhydrous ethanol and deionized water, and then placed in an electric constant temperature drying oven at 60° C. for 12 h to obtain silica nanowires.

[0024] Furthermore, in step S2.2, the volume ratio of the microemulsion to TEOS is 4:1.

[0025] Furthermore, step S3 of preparing magnetic silica nanowires comprises the following steps:

[0026] S3.1: immersing the silica nanowires in deionized water, ultrasonically dispersing for 1-1.5 hours, and then blowing with nitrogen for 30 minutes to dry, to obtain treated silica nanowires;

[0027] S3.2: FeCl3·6H2O and FeSO4·7H2O are mixed and added to 50 parts by weight of deionized water, purged with nitrogen for 30 minutes, and then the treated silica nanowires are added thereto, heated in a water bath to 30°C, stirred continuously, and during the stirring process, 20% of the total mass of ammonia water is added to the system until the pH value of the system reaches 12, to obtain a final mixture;

[0028] S3.3: The final mixture is then kept in a water bath at 65°C for 2 h, and finally washed thoroughly with water until neutral, and dried in a vacuum oven at 60°C for 12 h to obtain magnetic silica nanowires.

[0029] Furthermore, in step S3.1, the solid-liquid ratio of the silica nanowires to the deionized water is 1:10.

[0030] Furthermore, in step S3.2, the mass ratio of FeCl3·6H2O to FeSO4·7H2O is 1:5.

[0031] Furthermore, the concentration of aqueous ammonia in step S3.2 is 10-25wt%.

[0032] An early high-strength and low-rebound shotcrete material is prepared by any of the above-mentioned methods for preparing early high-strength and low-rebound shotcrete materials.

[0033] Compared with the prior art, the present invention has at least the following beneficial effects:

[0034] 1. The present invention adds sodium alginate and sodium carboxymethyl cellulose into the preparation of the modified accelerating setting agent. When sodium alginate encounters calcium ions, it can form a thermally irreversible gel. After being prepared into an accelerating setting agent, it can react with calcium in the concrete material to form a stable gel more quickly. Sodium carboxymethyl cellulose can significantly increase the viscosity of the solution, which helps to maintain the uniform distribution of solid particles in the system and prevent sedimentation. When sodium alginate and sodium carboxymethyl cellulose are used together, they can cooperate with each other. The colloidal network formed by sodium alginate can wrap and stabilize the particles of the dispersed phase, and sodium carboxymethyl cellulose further enhances the viscosity and stability of the dispersed system through the entanglement and interweaving between its polymer chains, thereby allowing the concrete material to quickly form a gel state, reduce rebound, and improve concrete strength.

[0035] 2. The present invention adds magnetic silica nanowires when preparing concrete materials. The magnetic silica nanowires are embedded or surface-modified magnetic particles, and the magnetic silica nanowires can be filled in the cement pores of the concrete material to form an integral gel material with the cement, thereby improving the density and durability of the concrete material. In addition, the magnetic silica nanowires can move, separate or arrange in a direction under the action of a magnetic field, thereby controlling the arrangement of the concrete material, and improving the strength of the concrete material by crack deflection and plastic deformation, reducing the destructive fracture of the concrete material, thereby improving the mechanical properties of the concrete material in a specific direction. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings, which are incorporated herein and constitute a part of the specification, illustrate embodiments of the present disclosure and, together with the description, further serve to explain the principles of the present disclosure and to enable those skilled in the relevant art to make and use the present disclosure.

[0037] Figure 1 The present invention is a flowchart of a method for preparing an early high-strength low-rebound shotcrete material used in an embodiment of the present invention. DETAILED DESCRIPTION

[0038] The following is a detailed description of an early high-strength low-rebound shotcrete material and a preparation method thereof provided by the present invention in combination with the accompanying drawings and specific embodiments. At the same time, it is explained here that in order to make the embodiments more detailed, the following embodiments are the best and preferred embodiments, and those skilled in the art may also adopt other alternative methods to implement some known technologies; and the accompanying drawings are only for a more specific description of the embodiments, and are not intended to specifically limit the present invention.

[0039] Embodiment 1:

[0040] A method for preparing early high-strength low-rebound shotcrete material, such as Figure 1 As shown, the following steps are included:

[0041] S1: Preparation of modified accelerating agent

[0042] S1.1: Take 50 parts by mass of fluorosilicic acid and add it into a reactor, and slowly add 25 parts by mass of aluminum hydroxide, and stir with a magnetic stirrer at 200 r / min for 30 minutes to obtain a suspension;

[0043] S1.2: Heat 200 parts by mass of deionized water to 60°C, add 84 parts by mass of aluminum sulfate while stirring, continue stirring until the aluminum sulfate is dissolved, then add 17 parts by mass of the suspension and 1.7 parts by mass of sodium aluminate, stir evenly, heat the solution to 80°C, keep warm and react for 30 minutes to obtain a reaction solution;

[0044] S1.3: Add 1 part by mass of sodium alginate and 2 parts by mass of sodium carboxymethyl cellulose to the reaction solution, and cool it at 0°C. Stir the mixture until it cools to room temperature to obtain an accelerating setting agent.

[0045] S1.4: Add 1.5% by mass of nano-silicon dioxide to the accelerating agent, wherein the diameter of the nano-silicon dioxide is 20-50 nm, and stir evenly to obtain a modified accelerating agent.

[0046] S2: Preparation of silica nanowires

[0047] S2.1: Mix ionized water, sodium citrate solution, anhydrous ethanol, 25% ammonia water and 50% polyvinylpyrrolidone ethanol solution in a volume ratio of 3:1:10:1:100 to obtain a microemulsion;

[0048] S2.2: TEOS was added to the microemulsion, the volume ratio of microemulsion to TEOS was 4:1, the temperature was raised to 40°C, and the mixture was centrifuged at a speed of 1000 r / min for 10 min and reacted for 4 h to obtain a white product;

[0049] S2.3: The white product was washed with anhydrous ethanol and deionized water, and then placed in an electric constant temperature drying oven at 60° C. for 12 h to obtain silica nanowires.

[0050] S3: Preparation of magnetic silica nanowires

[0051] S3.1: immersing the silica nanowires in deionized water, with the solid-liquid ratio of the silica nanowires to the deionized water being 1:10, ultrasonically dispersing for 1 hour, and then drying with nitrogen purge for 30 minutes to obtain treated silica nanowires;

[0052] S3.2: FeCl3·6H2O and FeSO4·7H2O are mixed and added to 50 parts by weight of deionized water, the mass ratio of FeCl3·6H2O to FeSO4·7H2O being 1:5, and the mixture is purged with nitrogen for 30 minutes, and then the treated silica nanowires are added thereto, and the mixture is heated in a water bath to 30°C, and stirred continuously. During the stirring process, 20% of the total mass of ammonia water is added to the mixture until the pH value of the system reaches 12, and the concentration of ammonia water is 25wt%, to obtain a final mixture;

[0053] S3.3: The final mixture is then kept in a water bath at 65°C for 2 h, and finally washed thoroughly with water until neutral, and dried in a vacuum oven at 60°C for 12 h to obtain magnetic silica nanowires.

[0054] S4: Preparation of early high-strength and low-rebound shotcrete materials

[0055] 100 parts by mass of silicate cement, 15 parts by mass of fly ash, 40 parts by mass of calcium carbonate, 1.5 parts by mass of carbon fiber, 7 parts by mass of magnetic silica nanowires, 15 parts by mass of polycarboxylate water reducer, 35 parts of modified accelerator and 150 parts by mass of mixing water were mixed for 30 minutes to obtain an early high-strength and low-rebound shotcrete material.

[0056] Embodiment 2:

[0057] A method for preparing early high-strength low-rebound shotcrete material, such as Figure 1 As shown, the following steps are included:

[0058] S1: Preparation of modified accelerating agent

[0059] S1.1: Take 50 parts by mass of fluorosilicic acid and add it into a reactor, and slowly add 25 parts by mass of aluminum hydroxide, and stir with a magnetic stirrer at 200 r / min for 30 minutes to obtain a suspension;

[0060] S1.2: Heat 200 parts by mass of deionized water to 60°C, add 85 parts by mass of aluminum sulfate while stirring, continue stirring until the aluminum sulfate is dissolved, then add 17 parts by mass of the suspension and 1.7 parts by mass of sodium aluminate, stir evenly, heat the solution to 80°C, keep warm and react for 30 minutes to obtain a reaction solution;

[0061] S1.3: Add 1 part by mass of sodium alginate and 2 parts by mass of sodium carboxymethyl cellulose to the reaction solution, and cool it at 0°C. Stir the mixture until it cools to room temperature to obtain an accelerating setting agent.

[0062] S1.4: Add 4.5% by mass of nano-silicon dioxide to the accelerating agent, wherein the diameter of the nano-silicon dioxide is 20-50 nm, and stir evenly to obtain a modified accelerating agent.

[0063] S2: Preparation of silica nanowires

[0064] S2.1: Mix ionized water, sodium citrate solution, anhydrous ethanol, 25% ammonia water and 50% polyvinylpyrrolidone ethanol solution in a volume ratio of 3:1:10:1:100 to obtain a microemulsion;

[0065] S2.2: TEOS was added to the microemulsion, the volume ratio of microemulsion to TEOS was 4:1, the temperature was raised to 40°C, and the mixture was centrifuged at a speed of 1000 r / min for 10 min and reacted for 4 h to obtain a white product;

[0066] S2.3: The white product was washed with anhydrous ethanol and deionized water, and then placed in an electric constant temperature drying oven at 60° C. for 12 h to obtain silica nanowires.

[0067] S3: Preparation of magnetic silica nanowires

[0068] S3.1: immersing the silica nanowires in deionized water, with the solid-liquid ratio of the silica nanowires to the deionized water being 1:10, ultrasonically dispersing for 1 hour, and then drying with nitrogen purge for 30 minutes to obtain treated silica nanowires;

[0069] S3.2: FeCl3·6H2O and FeSO4·7H2O are mixed and added into 50 parts by weight of deionized water, the mass ratio of FeCl3·6H2O to FeSO4·7H2O being 1:5, and nitrogen is purged for 30 minutes, and then the treated silica nanowires are added thereto, and the mixture is heated in a water bath to 30°C, and stirred continuously. During the stirring process, 20% of the total mass of ammonia water is added to the mixture until the pH value of the system reaches 12, and the concentration of ammonia water is 10wt%, to obtain a final mixture;

[0070] S3.3: The final mixture is then kept in a water bath at 65°C for 2 h, and finally washed thoroughly with water until neutral, and dried in a vacuum oven at 60°C for 12 h to obtain magnetic silica nanowires.

[0071] S4: Preparation of early high-strength and low-rebound shotcrete materials

[0072] 100 parts by mass of silicate cement, 10 parts by mass of fly ash, 15 parts by mass of calcium carbonate, 1 part by mass of carbon fiber, 4 parts by mass of magnetic silica nanowires, 10 parts by mass of polycarboxylate water reducer, 25 parts of modified accelerator and 200 parts by mass of mixing water were mixed for 30 minutes to obtain an early high-strength and low-rebound shotcrete material.

[0073] Embodiment 3:

[0074] A method for preparing early high-strength low-rebound shotcrete material, such as Figure 1 As shown, the following steps are included:

[0075] S1: Preparation of modified accelerating agent

[0076] S1.1: Take 50 parts by mass of fluorosilicic acid and add it into a reactor, and slowly add 25 parts by mass of aluminum hydroxide, and stir with a magnetic stirrer at 150 r / min for 35 min to obtain a suspension;

[0077] S1.2: Heat 200 parts by mass of deionized water to 65°C, add 84 parts by mass of aluminum sulfate while stirring, continue stirring until the aluminum sulfate is dissolved, then add 17 parts by mass of the suspension and 1.7 parts by mass of sodium aluminate, stir evenly, heat the solution to 85°C, keep the temperature for reaction for 40 minutes, and obtain a reaction solution;

[0078] S1.3: Add 1 part by mass of sodium alginate and 2 parts by mass of sodium carboxymethyl cellulose to the reaction solution, and cool it at 4°C. Stir the mixture until it cools to room temperature to obtain an accelerating setting agent.

[0079] S1.4: Add 1.5% by mass of nano-silicon dioxide to the accelerating agent, wherein the diameter of the nano-silicon dioxide is 20-50 nm, and stir evenly to obtain a modified accelerating agent.

[0080] S2: Preparation of silica nanowires

[0081] S2.1: Mix ionized water, sodium citrate solution, anhydrous ethanol, 25% ammonia water and 50% polyvinylpyrrolidone ethanol solution in a volume ratio of 3:1:10:1:100 to obtain a microemulsion;

[0082] S2.2: TEOS was added to the microemulsion, the volume ratio of microemulsion to TEOS was 4:1, the temperature was raised to 40°C, and the mixture was centrifuged at 800 r / min for 15 min and reacted for 4 h to obtain a white product;

[0083] S2.3: The white product was washed with anhydrous ethanol and deionized water, and then placed in an electric constant temperature drying oven at 60° C. for 12 h to obtain silica nanowires.

[0084] S3: Preparation of magnetic silica nanowires

[0085] S3.1: immersing the silica nanowires in deionized water, with the solid-liquid ratio of the silica nanowires to the deionized water being 1:10, ultrasonically dispersing for 1.5 hours, and then drying with nitrogen purge for 30 minutes to obtain treated silica nanowires;

[0086] S3.2: FeCl3·6H2O and FeSO4·7H2O are mixed and added to 50 parts by weight of deionized water, the mass ratio of FeCl3·6H2O to FeSO4·7H2O being 1:5, and the mixture is purged with nitrogen for 30 minutes, and then the treated silica nanowires are added thereto, and the mixture is heated in a water bath to 30°C, and stirred continuously. During the stirring process, 20% of the total mass of ammonia water is added to the mixture until the pH value of the system reaches 12, and the concentration of ammonia water is 25wt%, to obtain a final mixture;

[0087] S3.3: The final mixture is then kept in a water bath at 65°C for 2 h, and finally washed thoroughly with water until neutral, and dried in a vacuum oven at 60°C for 12 h to obtain magnetic silica nanowires.

[0088] S4: Preparation of early high-strength and low-rebound shotcrete materials

[0089] 100 parts by mass of silicate cement, 15 parts by mass of fly ash, 40 parts by mass of calcium carbonate, 1.5 parts by mass of carbon fiber, 7 parts by mass of magnetic silica nanowires, 15 parts by mass of polycarboxylate water reducer, 35 parts of modified accelerator and 150 parts by mass of mixing water were mixed for 35 minutes to obtain an early high-strength and low-rebound shotcrete material.

[0090] Comparative Example 1:

[0091] Compared with Example 1, the difference of Comparative Example 1 is that sodium alginate is not added in step S1, specifically, “S1.1: 50 parts by mass of fluorosilicic acid are added to a reactor, and 25 parts by mass of aluminum hydroxide are slowly added, and a magnetic stirrer is stirred at 200 r / min for 30 min to obtain a suspension;

[0092] S1.2: Heat 200 parts by mass of deionized water to 60°C, add 84 parts by mass of aluminum sulfate while stirring, continue stirring until the aluminum sulfate is dissolved, then add 17 parts by mass of the suspension and 1.7 parts by mass of sodium aluminate, stir evenly, heat the solution to 80°C, keep warm and react for 30 minutes to obtain a reaction solution;

[0093] S1.3: Add 3 parts by mass of sodium carboxymethyl cellulose to the reaction solution, and cool it at 0°C. Stir the mixture until it cools to room temperature to obtain an accelerating setting agent.

[0094] S1.4: Add 1.5% by mass of nano-silicon dioxide to the accelerating agent, wherein the diameter of the nano-silicon dioxide is 20-50 nm, and stir evenly to obtain a modified accelerating agent. The prepared early high-strength and low-rebound shotcrete material is recorded as Comparative Example 1.

[0095] Comparative Example 2:

[0096] Compared with Example 1, the difference of Comparative Example 2 is that sodium carboxymethyl cellulose is not added in step S1, specifically: "S1.1: 50 parts by mass of fluorosilicic acid are added to a reactor, and 25 parts by mass of aluminum hydroxide are slowly added, and a magnetic stirrer is stirred at 200 r / min for 30 minutes to obtain a suspension;

[0097] S1.2: Heat 200 parts by mass of deionized water to 60°C, add 84 parts by mass of aluminum sulfate while stirring, continue stirring until the aluminum sulfate is dissolved, then add 17 parts by mass of the suspension and 1.7 parts by mass of sodium aluminate, stir evenly, heat the solution to 80°C, keep warm and react for 30 minutes to obtain a reaction solution;

[0098] S1.3: Add 3 parts by mass of sodium alginate to the reaction solution, and cool it at 0°C. Stir the mixture until it cools to room temperature to obtain an accelerating setting agent.

[0099] S1.4: Add 1.5% by mass of nano-silicon dioxide to the accelerating agent, wherein the diameter of the nano-silicon dioxide is 20-50 nm, and stir evenly to obtain a modified accelerating agent. The prepared early high-strength low-rebound shotcrete material is recorded as Comparative Example 2.

[0100] Comparative Example 3:

[0101] Compared with Example 1, the difference of Comparative Example 3 is that sodium alginate and sodium carboxymethyl cellulose are not added, specifically: “S1.1: 50 parts by mass of fluorosilicic acid are added to a reactor, and 25 parts by mass of aluminum hydroxide are slowly added, and a magnetic stirrer is stirred at 200 r / min for 30 min to obtain a suspension;

[0102] S1.2: Heat 200 parts by mass of deionized water to 60°C, add 84 parts by mass of aluminum sulfate while stirring, continue stirring until the aluminum sulfate is dissolved, then add 17 parts by mass of the suspension and 1.7 parts by mass of sodium aluminate, stir evenly, heat the solution to 80°C, keep warm and react for 30 minutes to obtain a reaction solution;

[0103] S1.3: Cool the reaction solution at 0°C and keep stirring during the cooling process until it cools to room temperature to obtain an accelerating setting agent;

[0104] S1.4: Add 1.5% by mass of nano-silicon dioxide to the accelerating agent, wherein the diameter of the nano-silicon dioxide is 20-50 nm, and stir evenly to obtain a modified accelerating agent. The prepared early high-strength and low-rebound shotcrete material is recorded as Comparative Example 3.

[0105] Comparative Example 4:

[0106] Compared with Example 1, the difference of Comparative Example 4 is that no magnetic silica nanowires are added in step S4, specifically: "S4: Preparation of early high-strength low-rebound shotcrete material

[0107] 100 parts by mass of Portland cement, 15 parts by mass of fly ash, 40 parts by mass of calcium carbonate, 1.5 parts by mass of carbon fiber, 15 parts by mass of polycarboxylate water reducer, 35 parts by mass of modified accelerator and 150 parts by mass of mixing water were mixed and stirred for 30 min to obtain an early high-strength and low-rebound shotcrete material. The prepared early high-strength and low-rebound shotcrete material was recorded as Comparative Example 4.

[0108] The compressive strength values ​​of Examples 1-3 and Comparative Examples 1-4 were measured using standard test methods according to JTGE30-2005.

[0109] Table 1

[0110]

[0111] The compressive strengths of Examples 1-3 are 43.45 MPa, 42.98 MPa and 43.18 MPa, respectively. Among them, the compressive strength of Example 1 is the highest among all samples, and the slump of Example 1 is 20 mm, which is also the lowest among all samples. It can be seen that Example 1 is the best mix ratio.

[0112] The compressive strength of comparative example 1 is 33.61 MPa, the compressive strength of comparative example 2 is 32.29 MPa, and the compressive strength of comparative example 3 is 26.74 MPa. It can be seen that both sodium alginate and sodium carboxymethyl cellulose have the function of enhancing the viscosity and stability of the dispersion system, thereby allowing the concrete material to quickly form a gel state to reduce rebound and improve the strength of the concrete. When the two are used in synergy, the effect is further improved than that of using a single one.

[0113] The compressive strength of Comparative Example 4 is 27.67 MPa. It can be seen that the addition of magnetic silica nanowires improves the mechanical properties of the concrete material in a specific direction, thereby improving the compressive strength of the concrete material.

[0114] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing an early high-strength low-rebound shotcrete material, characterized in that: The steps include: S1: Preparation of modified accelerating agent Fluorosilicic acid is added to a reactor, and aluminum hydroxide is slowly added, and magnetic stirring is performed to obtain a suspension, deionized water is heated, aluminum sulfate is added, and then the suspension and sodium aluminate are added, and the mixture is stirred evenly and heated to react to obtain a reaction solution, sodium alginate and sodium carboxymethyl cellulose are added to the reaction solution, and the reaction solution is cooled, and stirring is maintained during the cooling process until the reaction solution is cooled to room temperature to obtain an accelerating setting agent, and nano-silicon dioxide is added to the accelerating setting agent, and the mixture is stirred evenly to obtain a modified accelerating setting agent; S2: Preparation of silica nanowires Mixing ionized water, sodium citrate solution, anhydrous ethanol, 25% ammonia water and 50% polyvinyl pyrrolidone ethanol solution to obtain a microemulsion, adding TEOS to the microemulsion, heating the reaction to obtain a white product, washing the white product with anhydrous ethanol and deionized water, and drying to obtain silica nanowires; S3: Preparation of magnetic silica nanowires The silica nanowires are immersed in deionized water, ultrasonically dispersed, and purged with nitrogen to obtain treated silica nanowires, FeCl3·6H2O and FeSO4·7H2O are mixed and added to deionized water, purged with nitrogen, and then the treated silica nanowires are added thereto, heated in a water bath, and ammonia water is added during stirring to obtain a final mixture, and then the final mixture is kept in a water bath at 65° C. for 2 hours, and finally thoroughly washed with water to neutrality, and dried to obtain magnetic silica nanowires; S4: Preparation of early high-strength and low-rebound shotcrete materials 100 parts by mass of silicate cement, 10-15 parts by mass of fly ash, 15-40 parts by mass of calcium carbonate, 1-1.5 parts by mass of carbon fiber, 4-7 parts by mass of magnetic silica nanowires, 10-15 parts by mass of polycarboxylate water reducer, 25-35 parts by mass of modified accelerator and 150-200 parts by mass of mixing water are mixed for 30-35 minutes to obtain an early high-strength low-rebound shotcrete material.

2. The method for preparing an early high-strength low-rebound shotcrete material according to claim 1, characterized in that: Step S1: preparing a modified quick-setting agent, comprising the following steps: S1.1: Take 50 parts by mass of fluorosilicic acid and add it into a reactor, and slowly add 25 parts by mass of aluminum hydroxide, stir with a magnetic stirrer at 150-200 r / min for 30-35 min to obtain a suspension; S1.2: Heat 200 parts by weight of deionized water to 60-65°C, add 84-85 parts by weight of aluminum sulfate while stirring, continue stirring until the aluminum sulfate is dissolved, then add 17 parts by weight of the suspension and 1.7 parts by weight of sodium aluminate, stir evenly, heat the solution to 80-85°C, keep warm and react for 30-40 minutes to obtain a reaction solution; S1.3: Add 1 part by mass of sodium alginate and 2 parts by mass of sodium carboxymethyl cellulose to the reaction solution, and cool it at 0-4°C. Stir the mixture until it cools to room temperature to obtain an accelerating setting agent. S1.4: Add 1.5-4.5% by mass of nano-silicon dioxide to the accelerating setting agent, stir evenly, and obtain a modified accelerating setting agent.

3. The method for preparing an early high-strength low-rebound shotcrete material according to claim 2, characterized in that: The diameter of the nano-silica in step S1.4 is 20-50 nm.

4. The method for preparing an early high-strength low-rebound shotcrete material according to claim 3, characterized in that: Step S2 is to prepare silicon dioxide nanowires, comprising the following steps: S2.1: Mix ionized water, sodium citrate solution, anhydrous ethanol, 25% ammonia water and 50% polyvinylpyrrolidone ethanol solution in a volume ratio of 3:1:10:1:100 to obtain a microemulsion; S2.2: Add TEOS to the microemulsion, raise the temperature to 40°C, and centrifuge at 800-1000 r / min for 10-15 min, react for 4 h, and obtain a white product; S2.3: The white product was washed with anhydrous ethanol and deionized water, and then placed in an electric constant temperature drying oven at 60° C. for 12 h to obtain silica nanowires.

5. The method for preparing an early high-strength low-rebound shotcrete material according to claim 4, characterized in that: The volume ratio of microemulsion to TEOS in step S2.2 is 4:

1.

6. The method for preparing an early high-strength low-rebound shotcrete material according to claim 5, characterized in that: Step S3 is to prepare magnetic silica nanowires, comprising the following steps: S3.1: immersing the silica nanowires in deionized water, ultrasonically dispersing for 1-1.5 hours, and then blowing with nitrogen for 30 minutes to dry, to obtain treated silica nanowires; S3.2: FeCl3·6H2O and FeSO4·7H2O are mixed and added to 50 parts by weight of deionized water, purged with nitrogen for 30 minutes, and then the treated silica nanowires are added thereto, heated in a water bath to 30°C, stirred continuously, and during the stirring process, 20% of the total mass of ammonia water is added to the system until the pH value of the system reaches 12, to obtain a final mixture; S3.3: The final mixture is then kept in a water bath at 65°C for 2 h, and finally washed thoroughly with water until neutral, and dried in a vacuum oven at 60°C for 12 h to obtain magnetic silica nanowires.

7. The method for preparing an early high-strength low-rebound shotcrete material according to claim 6, characterized in that: The solid-to-liquid ratio of the silica nanowires to the deionized water in step S3.1 is 1:

10.

8. The method for preparing an early high-strength low-rebound shotcrete material according to claim 7, characterized in that: The mass ratio of FeCl3·6H2O to FeSO4·7H2O in step S3.2 is 1:

5.

9. The method for preparing an early high-strength low-rebound shotcrete material according to claim 8, characterized in that: The concentration of aqueous ammonia in step S3.2 is 10-25 wt%.

10. An early high-strength and low-rebound shotcrete material, which is prepared by the method for preparing an early high-strength and low-rebound shotcrete material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Low-dosage high-early-strength alkali-free liquid accelerator and preparation method thereof

    CN111333362A

  • High-strength alkali-free liquid accelerator and preparation method thereof

    CN112456853A

  • Alkali-free accelerator as well as preparation method and application thereof

    CN113121150A

  • Anti-disturbance cement-based repairing material and preparation method thereof

    CN116496055A

  • Anticorrosive paint and coating

    CN116535943A

Cited By

  • Anti-cracking and rebound-reducing tunnel sprayed concrete and preparation and use method of anti-cracking and rebound-reducing tunnel sprayed concrete

    CN120172707A